Japanese National Festivals - Zarina, Soliyeva; Marvarid, Rajabova (International Journal on Integrated Education, 2023)
The article discusses some of Japan's national holidays. Information about when and how the holidays will be held is shown. There is also extensive material about the Japanese people.